1999
DOI: 10.1093/rheumatology/38.10.974
|View full text |Cite
|
Sign up to set email alerts
|

Steroid injection for heel pain: evidence of short-term effectiveness. A randomized controlled trial

Abstract: A steroid injection can provide relief from heel pain in the short term. There appears to be no increase in patient comfort from anaesthetizing the heel prior to infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(123 citation statements)
references
References 12 publications
8
114
0
1
Order By: Relevance
“…All of the included studies compared corticosteroid injection and placebo injection in the treatment of plantar fasciitis. Two studies were performed in UK (7,10), one in Australia (8) and one in Kenya (9). The patients in the included studies were middle-aged and elderly, with an average age of between 43.1 and 58.2 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the included studies compared corticosteroid injection and placebo injection in the treatment of plantar fasciitis. Two studies were performed in UK (7,10), one in Australia (8) and one in Kenya (9). The patients in the included studies were middle-aged and elderly, with an average age of between 43.1 and 58.2 years.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The follow-up duration varied among the included studies, and the results were pooled based on different follow-up durations. The VAS scores after one, two and three month(s) were reported in three (7-9), two (8,9) and three (7,8,10) studies, respectively. The results showed that pain relief was achieved after one month by corticosteroid injection (SMD, -0.32; 95% CI, -0.59--0.06; P=0.02) (Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] In a study by Li et al, [20] treatment with steroid injections had-a significant effect only at the 1-month, and not the 6-or 12-month, follow-ups. In a randomized controlled study involving 106 patients, Crawford et al [21] reported that CS injections were superior to placebo at 1 month, but not at subse- PAIN A RI quent follow-up assessments. In another randomized study, Ball et al [22] reported that CS injection had short-and medium-term benefits in a study involving 65 patients with plantar fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are evidences of therapeutic ultrasound, laser and iontophoresis being used as a treatment method for plantar fasciitis [14,15], the best results have been found with extracorporeal shock wave therapy (ESWT) [16]. ESWT uses pulses of high-pressure sound waves on damaged tissue to relieve pain associated with PF.…”
Section: Electrotherapymentioning
confidence: 99%